Developmental Trajectories of Parental Self-Efficacy as Children Transition to Adolescence in Nine Countries: Latent Growth Curve Analyses - Buchanan, Christy M. (Archīum Ateneo, 2023)
Little is known about the developmental trajectories of parental self-efficacy as children transition into adolescence. This study examined parental self-efficacy among mothers and fathers over 3 1/2 years representing this transition, and whether the level and developmental trajectory of parental self-efficacy varied by cultural group. Data were drawn from three waves of the Parenting Across Cultures (PAC) project, a large-scale longitudinal, cross-cultural study, and included 1178 mothers and 1041 fathers of children who averaged 9.72 years of age at T1 (51.2% girls). Parents were from nine countries (12 ethnic/cultural groups), which were categorized into those with a predominant collectivistic (i.e., China, Kenya, Philippines, Thailand, Colombia, and Jordan) or individualistic (i.e., Italy, Sweden, and USA) cultural orientation based on Hofstede’s Individualism Index (Hofstede Insights, 2021). Latent growth curve analyses supported the hypothesis that parental self-efficacy would decline as children transition into adolescence only for parents from more individualistic countries; parental self-efficacy increased over the same years among parents from more collectivistic countries. Secondary exploratory analyses showed that some demographic characteristics predicted the level and trajectory of parental self-efficacy differently for parents in more individualistic and more collectivistic countries. Results suggest that declines in parental self-efficacy documented in previous research are culturally influenced.